2020
DOI: 10.1007/s13346-020-00848-8
|View full text |Cite
|
Sign up to set email alerts
|

Exploration into the opinions of patients with HIV, healthcare professionals and the lay public of the use of microneedles in clinical practice: highlighting the translational potential for their role in HIV infection

Abstract: Poor adherence to oral antiretroviral therapy (ART) remains an important challenge in the treatment of HIV. Microneedles (MN) potentially could offer a non-invasive long-acting (LA) delivery approach, avoiding the need for daily dosing of ART. However, this claim has yet to be explored amongst its potential end-users. The aim of this mixed methods study was to investigate the perspectives from various end-users surrounding the translation of MN technology to general clinical practice, with a particular focus o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 45 publications
(81 reference statements)
0
12
0
Order By: Relevance
“…In different study, McCrudden et al [322] have also found that intravaginal delivery of rilpivirine using dissolving MN was able to give in vivo plasma concentration at approximately 115 ng/ml at the day 56 endpoint. In terms of MN acceptability for treatment of HIV, Moffatt et al [323] has recently published the first paper which provided the insights of patients with HIV, healthcare professionals and members of lay public on the potential of MN for delivery of ARV drugs. Based on their research, it was known that both participants and respondents gave positive response on the MN application for treatment of HIV.…”
Section: Current Trend and Prospective Applications Of Microneedlesmentioning
confidence: 99%
See 1 more Smart Citation
“…In different study, McCrudden et al [322] have also found that intravaginal delivery of rilpivirine using dissolving MN was able to give in vivo plasma concentration at approximately 115 ng/ml at the day 56 endpoint. In terms of MN acceptability for treatment of HIV, Moffatt et al [323] has recently published the first paper which provided the insights of patients with HIV, healthcare professionals and members of lay public on the potential of MN for delivery of ARV drugs. Based on their research, it was known that both participants and respondents gave positive response on the MN application for treatment of HIV.…”
Section: Current Trend and Prospective Applications Of Microneedlesmentioning
confidence: 99%
“…Each of the studies mentioned outlines in detail a series of positive aspects for patients of MN delivery of ARV drugs. To maximise the use of MN for HIV treatment, it is imperative to give prior knowledge and education to the patients and healthcare professionals about the safety and the clinical applications of MN [323].…”
Section: Current Trend and Prospective Applications Of Microneedlesmentioning
confidence: 99%
“…In particular, in low-resource settings where the number of trained medical staff is limited, potential self-administration could be of great interest. 94 , 96 …”
Section: La-art Agents Based On Novel Pharmaceutical Formulationsmentioning
confidence: 99%
“…Partners in academia and industry have provided substantial evidence to show appropriate MN usability across various populations (Norman et al, 2014), highlighting significant benefits for patients, the public, and healthcare professionals (Moffatt, Quinn, McCague, & Donnelly, 2020). Moving forward toward clinical progression, regulatory bodies (e.g., the US FDA and the MHRA in the UK) will need to provide minimum standards with respect to MN manufacturing.…”
Section: Microneedle Technologymentioning
confidence: 99%